Relationship Of Sleep Quality With Fatigue In Chronic Obstructive Pulmonary Disease (COPD) Patients At Rantauprapat Regional General Hospital - Siburian, Christine Handayani; Naibaho, Eka Nugraha V; Silaban , Nataria Yanti (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a preventable and treatable disease characterized by persistent respiratory symptoms and airflow limitation. Disturbed sleep will not be able to restore and restore the condition of his body and cannot rest his body properly. This situation results in irritability, fatigue, dizziness, anxiety, and stress so that it will affect the quality of life of the patient. The purpose of this study was to identify the relationship between quality of life and fatigue in patients with Chronic Obstructive Pulmonary Disease (COPD) at the Rantau Prapat Regional General Hospital. The design of this study was quantitative with a cross sectional approach. The number of samples was 30 people with accidental sampling technique. The results of the study obtained the result of p value = 0.004. These figures show a very strong correlation between sleep quality and fatigue in patients COPD received. It is suggested that the results of this study can be used as policy-making material in improving health services for patients with Chronic Obstructive Pulmonary Disease (COPD).